Pentingnya Perhitungan Biaya Produksi Untuk Penentuan Harga Jual Produk Aneka Kripik - Jeanne Asteria Wawolangi; Anita Permatasari (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2021)
The micro business is a marginal business type characterized by the use ofrelatively simple technology, a relatively small nominal level of capital, low accessto credit, and oriented towards local market needs. General problem faced inmanaging this business is the calculation of product costs, which are usually onlycalculated simply based on the purchase price of raw materials, while directproduction costs, because what is important is the smooth sale of these products. This study aims to assist micro-entrepreneurs in determining product costs, making it easier for business actors to determine the selling price of their products. This study uses a qualitative method.